Analisis Suhu Dan Konsentrasi Karbondioksida dalam Kotak Pendingin Terhadap Susut Bobot dan Umur Simpan Buah Nanas (Ananas Comosus L. Merr) Berbasis MIT App Inventor 2 - Yulinda Nugraeni; Sri Wahyu Suciyati; Gurum Ahmad Pauzi; Amir Supriyanto (Journal of Energy, Material, and Instrumentation Technology, 2020)
Shrinkage of weight loss and shelf life of pineapples is influenced by high temperatures and CO2 concentrations. This study aims to analyze the influence of temperature and CO2 concentration on weight loss and shelf life pineapple in a fridge cooler. The analysis data is obtained from a monitoring tool that has even the ESP8266 module to connect the Arduino with wifi through an application made with MIT App Inventor 2 so that data can be displayed with android. The downside of this application is that if the cellular data network is weak or non-existent, data recording will stop. The results showed that the monitoring tool was able to send data successfully. During data collection, the temperature was 7.82oC - 11.05oC, the CO2 concentration was 457.20 ppm - 490.77 ppm, the weight loss on ripe pineapple was 1.84%, 2.63%, and the weight loss on raw fruit 1.36% - 3.52%. Then from these data the CO2 concentration affects the respiration process, respiration affects the decay process. Whereas temperature affects the physical changes of pineapple fruit so that the shelf life of pineapples can last up to 22 days.